TAXATION OF PERSONAL INCOMES IN ROMANIA: PRESENT AND PERSPECTIVES - Daniela PIRVU; Carmen Mihaela MOGOIU; Claudia STANCIU-TOLEA (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
The personal income tax is not only as an important revenue instrument but also as an instrument of national policy. Taxation of personal income in European Union countries is regulated usually by a progressive rate structure. This article aims to highlight the differences between Romania and other EU member states in the field of personal income tax and to raise the issue of reforming the tax system by introducing the tax household.